Quercetin may repair the impaired oxidant-antioxidant balance in 1, 2, 3, 4-tetrachlorodibenzo-p-dioxin induced cardiac injury in male rats - Nanakali, Nadir Mustafa (Cellular and Molecular Biology, 2020)
The purpose of this study was to evaluate the prophylactic effects of quercetin (QUE) against oxidative damages and histological changes induced by 1, 2, 3, 4-tetrachlorodibenzo-p-dioxin (TCDD) in rat heart. For this purpose, 20 adult male Wistar rats were divided into four groups as fellow control group, TCDD group (10µg/kg BW/day by gavage daily for 60 consecutive days), QUE group (30 mg/kg BW/day) and TCDD + QUEgroup. The oxidative biomarkers of heart tissue and the levels of cTnI and lipid profile in serum were measured. Our results showed that the cTnI serum level and the heart lipid peroxidation significantly increased and the heart level of antioxidant profile significantly decreased in the TCDD group compared to control and QUEgroups. While pretreatment with QUEcould significantly improved these factors in serum and heart tissue in animals that consumed TCDD. It can be concluded that QUEat doses of 30 mg/kg/day could alleviate heart oxidative damage and histological changes induced by TCDD.